USING INTERACTIVE METHODS IN TEACHING THE TOPIC "ELASTIC FORCES. HOOKE'S LAW" - Mahmudova Dilafruz Hasanovna,; Maxsutova Nilufar Kuanishovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article examines the application of interactive teaching methods in presenting the physics topic “Elastic Forces and Hooke’s Law.” Special attention is given to the effectiveness of modern pedagogical approaches in improving students’ understanding and engagement during the learning process. The study highlights the use of the “INSERT” method as an innovative instructional strategy that encourages active participation, critical thinking, and independent analysis among learners. Through this method, complex physical concepts related to elasticity and Hooke’s Law can be explained in a broader and more comprehensive manner. The article also emphasizes the importance of interactive technologies in increasing the quality and effectiveness of physics education.